Analysis of Didactic Situations: A Cross-Sectional Study between Natural Sciences, Language and Mathematics - Edilmer Jiménez Anicharico,; José Gregorio Arrieta Serrano,; Erica Estebana Baldovino Mercado,; Andrés Felipe Carvajal Orrego,; Carlos Carlos Moscote Fuentes,; Jaime Luis Fernández Arias, (International Journal of Medical Toxicology and Legal Medicine, 2024)
This paper shows the results of a research carried out within the framework of a pedagogical chair on science education for elementary school students in the city of Valledupar. One of the purposes of the research was to carry out an analysis of different situations of teaching natural sciences, which managed not only to promote these specific learnings, but also those corresponding to language and mathematics. Within this framework, a methodological device was organized to jointly analyze three didactic sequences designed by teachers who had participated in previous years in the referred subject. The authors consider that this type of initiative could favor the conceptual understanding and motivation of future teachers towards inclusive proposals, avoiding falling into the opposition between the teaching of natural sciences and that of language and mathematics, allow us to see a worrying persistence of problems of comprehension and production of texts among graduates in general and particularly among graduates oriented to the continuation of studies in disciplines in particular disciplines associated with education. This recognition does not seem to translate into actions to promote integrated work between teachers of the different teaching languages, as is the work of teachers of all disciplines related to training in reading comprehension.